Tuning Colossal Magnetoresistance Effect Through Chemical Substitution In Perovskite Manganites - Khatarkar, Subhash; Ahirwar, Kamlesh (International Journal of Membrane Science and Technology, 2023)
Objective: This research is focused on the colossal magnetoresistance (CMR) effect tunability via chemical substitution in perovskite manganites. The objective is to learn how changing the chemical structure of these compounds affect their magnetic and electronic characteristics particularly the CMR effect. Methods: Perovskite manganite materials were prepared by the chemical substitution method to tune the composition of transition metal ions and rare-earth elements. The structural, magnetic, and electronic characterizations were done by the means of X-ray diffraction, magnetization measurements, and electrical transport measurements. Results: The study showed that the selective chemical substitution within the perovskite structure could be used to modulate the CMR effect in manganite materials. Due to the differences in chemical structure the magnetic ordering, charge carrier concentration and electronic band structure are altered which in turn influence the magnitude of the CMR effect. For example, specific chemical substitutions were shown to remarkably strengthen the CMR effect, leading to better magnetoresistance characteristics. Conclusion: This study demonstrates the possibility of tuning the CMR effect by the chemical substitution of Mn perovskite materials. By manipulating the chemical composition, it is achievable to fine-tune the magnetic and electronic characteristics for various spintronics, magnetic sensors and other devices that need high magnetoresistance effects. The results help to gain more knowledge about CMR in manganite systems and provide the guidance for the research on improving their performance.